2020
DOI: 10.3390/molecules25030594
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Its Metabolites in Atherosclerosis Development

Abstract: Gut microbiota metabolites have a great influence on host digestive function and body health itself. The effects of intestinal microbes on the host metabolism and nutrients absorption are mainly due to regulatory mechanisms related to serotonin, cytokines, and metabolites. Multiple studies have repeatedly reported that the gut microbiota plays a fundamental role in the absorption of bioactive compounds by converting dietary polyphenols into absorbable bioactive substances. Moreover, some intestinal metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 76 publications
1
29
0
Order By: Relevance
“…Recent studies suggest that the gut microbiota leads to the development of atherosclerosis and the pre-atherogenic power of TMAO has already been demonstrated in studies that have come to prove that this compound is able to modify the metabolism of cholesterol and sterol, suppressing the reverse transport of cholesterol. 24 This leads to an accumulation of cholesterol in the macrophages, promoting the activation of the endothelial cells and the migration of foam cells to the walls of the arteries, triggering the platelet activation. 9 , 25 …”
Section: Resultsmentioning
confidence: 99%
“…Recent studies suggest that the gut microbiota leads to the development of atherosclerosis and the pre-atherogenic power of TMAO has already been demonstrated in studies that have come to prove that this compound is able to modify the metabolism of cholesterol and sterol, suppressing the reverse transport of cholesterol. 24 This leads to an accumulation of cholesterol in the macrophages, promoting the activation of the endothelial cells and the migration of foam cells to the walls of the arteries, triggering the platelet activation. 9 , 25 …”
Section: Resultsmentioning
confidence: 99%
“…The microbiota is recognized for its role in the production of beneficial SCFAs and their functions in the regulation of complex chronic inflammatory diseases such as atherosclerosis. A link between the microbiota and atherosclerosis emerged from studies of TMAO [ 13 , 14 , 15 ].…”
Section: Microbiota-derived Metabolites Associated With Atherosclementioning
confidence: 99%
“…Thus, mediators from the intestine reach suprasegmentals centers of the ANS and activate the work of sympathetic and parasympathetic divisions, thereby closing the pathological circle of the intestinal microbiota participation in the CVD pathogenesis. Numerous publications demonstrate that an increase in microbiota-mediated inflammatory mediators aggravates the course and prognosis of disease in CVD [ 138 , 139 , 140 , 141 ]. It is also found that the correction of the intestinal microbiota in patients with CVD improves the prognosis of the disease.…”
Section: The Neuroimmune Axis: Microbiota–intestine–brain-cvdmentioning
confidence: 99%